2015
DOI: 10.1073/pnas.1504986112
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of protonation states and visualization of hydrogen bonding in a glycoside hydrolase with neutron crystallography

Abstract: Glycoside hydrolase (GH) enzymes apply acid/base chemistry to catalyze the decomposition of complex carbohydrates. These ubiquitous enzymes accept protons from solvent and donate them to substrates at close to neutral pH by modulating the pK a values of key side chains during catalysis. However, it is not known how the catalytic acid residue acquires a proton and transfers it efficiently to the substrate. To better understand GH chemistry, we used macromolecular neutron crystallography to directly determine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 60 publications
5
48
0
Order By: Relevance
“…7a,b). This particular conformation for Glu176/Tyr72 has been observed before in the neutron crystal structure of T. reesei Xyn11 at pD4–4.4 with an empty active site (PDB 4s2f), which was shown to be able to return to a catalytically competent conformation at basic pD values [40, 42].
Fig.
…”
Section: Resultssupporting
confidence: 69%
“…7a,b). This particular conformation for Glu176/Tyr72 has been observed before in the neutron crystal structure of T. reesei Xyn11 at pD4–4.4 with an empty active site (PDB 4s2f), which was shown to be able to return to a catalytically competent conformation at basic pD values [40, 42].
Fig.
…”
Section: Resultssupporting
confidence: 69%
“…When the Nδ2 nitrogen of the imidic acid form of Asn92 extracts a proton from the attacking water, the proton is immediately transferred to the scissile glycosidic bond of substrate through the hydrogen bond network. Meanwhile, in xylanase of GH11, the general acid/base Glu177 receives a proton from the bulk solvent by altering its side‐chain conformation which enables to increase the p K a value of Glu177 . In the present neutron structure analysis of T26H, we found that the Arg145 residue interacting with Glu11 can play an important role in the protonation of the general acid/base in the retaining hydrolysis [Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Based on this observation, we suggest that the proton to be used for the protonation of Glu11 would be supplied by the hydronium ion (Scheme , left). Such proton transfer was also proposed for xylanase, a GH family 11 member . The resulting water molecule can be released to the bulk solvent when the substrate approaches to the active site cleft since it occupies a part of the subsite.…”
Section: Discussionmentioning
confidence: 92%
“…To probe the structural changes that occur upon internal aldimine SB protonation, we obtained a low-pH X-ray structure of AAT in the absence of substrate, in which both chains are in the internal aldimine state. Acidifying AAT crystals with acetic acid vapour, using a procedure described previously 23 , 24 , yielded a 1.9 Å room temperature X-ray structure at pH ~4.0 (PDB ID 5VK7; Table 1 ). When the geometries of the internal aldimines (chain B) from the pH 7.5 and pH 4.0 structures were compared, two major differences were evident.…”
Section: Resultsmentioning
confidence: 99%